2018
DOI: 10.1002/ejsp.2495
|View full text |Cite
|
Sign up to set email alerts
|

The role of system identity threat in conspiracy theory endorsement

Abstract: Conspiracy theories (CTs) about government officials and the institutions they represent are widespread, and span the ideological spectrum. In this study, we test hypotheses suggesting that system identity threat, or a perception that society's fundamental, defining values are under siege due to social change, will predict conspiracy thinking. Across two samples (N = 870, N = 2,702), we found that system identity threat is a strong predictor of a general tendency toward conspiracy thinking and endorsement of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
53
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 68 publications
3
53
0
1
Order By: Relevance
“…This illusion of explanatory depth has been examined in a broad range of areas (e.g., Rozenblit & Keil, 2002), but a paucity of research has investigated these processes in political domains (but see Fernbach et al, 2013)-an inherently abstruse yet consequential context (e.g., Conover & Feldman, 1989;Delli Carpini & Keeter, 1996;Vitriol, Reifen Tagar, & Federico, 2017;Wilson & Keil, 1998). Conspiratorial beliefs serve as explanations for complex, ambiguous, and threatening political phenomena (e.g., Graeupner & Coman, 2017;Miller, Saunders, & Farhart, 2016;Sunstein & Vermeule, 2009;Swami & Coles, 2010;Uscinski & Parent, 2014;Federico, Williams, Vitriol, 2017). Accordingly, we reasoned that illusions of explanatory depth for political phenomena would be uniquely related to endorsement of conspiratorial beliefs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This illusion of explanatory depth has been examined in a broad range of areas (e.g., Rozenblit & Keil, 2002), but a paucity of research has investigated these processes in political domains (but see Fernbach et al, 2013)-an inherently abstruse yet consequential context (e.g., Conover & Feldman, 1989;Delli Carpini & Keeter, 1996;Vitriol, Reifen Tagar, & Federico, 2017;Wilson & Keil, 1998). Conspiratorial beliefs serve as explanations for complex, ambiguous, and threatening political phenomena (e.g., Graeupner & Coman, 2017;Miller, Saunders, & Farhart, 2016;Sunstein & Vermeule, 2009;Swami & Coles, 2010;Uscinski & Parent, 2014;Federico, Williams, Vitriol, 2017). Accordingly, we reasoned that illusions of explanatory depth for political phenomena would be uniquely related to endorsement of conspiratorial beliefs.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research investigating the psychology of conspiracy beliefs has examined the role of personality characteristics or other individual differences (e.g., Abalakina-Paap, Stephan, Craig, & Gregory, 1999;Swami et al, 2011), political or social disenfranchisement (e.g., Federico, Williams, & Vitriol, 2017;Graeupner & Coman, 2017;Uscinski & Parent, 2014), conspiratorial mindsets (Imhoff & Bruder, 2014), and identity-based motivated-reasoning processes (e.g., Carey, Nyhan, Valentino, & Liu, 2016). These findings point to many dispositional and situational factors that increase endorsement of conspiracy beliefs-including perceived lack of control, heightened need for uniqueness, high individual narcissism coupled with low self-esteem, powerlessness, low political knowledge, interpersonal and political distrust, disagreeableness, paranoid cognitions and sinister attributions, and superstitious ideation-particularly when adopting such perspectives satisfies important psychological and ideological needs for order, certainty, and control (Berinsky, 2012;Cichocka, Marchlewska, Golec de Zavala, & Olechowski, 2016; for a review, see Douglas, Sutton, & Cichocka, 2017;Imhoff & Lamberty, 2017;Jost, Federico, & Napier, 2009;Miller et al, 2016;Lantian, Muller, Nurra, & Douglas, 2017;Sunstein, 2014;Swami & Coles, 2010;Van Prooijen, Krouwel, & Pollet, 2015;).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both correlational and experimental studies extensively support the emotional nature of belief in conspiracy theories. For instance, conspiracy beliefs are correlated with trait anxiety (Grzesiak-Feldman, 2013), and are predicted by the perception that society is under threat (Jolley, Douglas, & Sutton, 2018), and that society's fundamental values are changing (Federico, Williams, & Vitriol, 2018). Experimental studies have found that inducing a lack of control increases people's belief in organizational conspiracy theories (Whitson & Galinsky, 2008) and political conspiracy theories (Van Prooijen & Acker, 2015).…”
Section: Principle 3: Conspiracy Beliefs Are Emotionalmentioning
confidence: 99%
“…Next, research on the emotional roots of conspiracy belief is restricted to experimentally inducing experiences of threat (e.g., Jolley et al, 2018;Van Prooijen & Acker, 2015;Whitson & Galinsky, 2008) or to measuring threatening or emotional experiences (e.g., Jolley et al, 2018;Federico et al, 2018;Grzesiak-Feldman, 2013). We would advocate more sophisticated methodologies to study emotions, and particularly recommend a physiological approach to understand the relationship between emotions and belief in conspiracy theories.…”
Section: Future Researchmentioning
confidence: 99%